John Sturzaker interviewed by Rob Willis in the Rob and Olya Willis folklore collection - Sturzaker, John, 1935-2018.; Willis, Rob, 1944-; Willis, Olya. (1994)
Folkloric recording.
1. Conversation: Sturzaker speaks of his proud parents with his father as a general labourer, went to school until age 15, his love of the bush, parents very supportive, how strict the teachers were about discipline, how neither his parents could read. 2. Recitation: Old Black Joe (fragment). 3. The boy stood on the burning deck (WWI song). 4. Conversation: recalls 1939, how his father's side of the family played music, how the family had migrated out on the ship "White Heather", his family were German and Norwegian in origin, how he picked up tunes from old records as well as school music lessons, started going to dances at age 18 provided he was home on time, how he started playing for dances. 5. Schottische (waltz).
Recorded with Olya Willis.
Recorded on May 18, 1994 in Westbury, Tas.
Also available online
National Library of Australia Oral History & Indigenous Programs collection at ORAL TRC 6936/24.
Time-coded summary available
Keywords: Sturzaker, John, -- 1935-2018 -- Interviews; Folk musicians -- Tasmania -- Interviews; Dance music -- Tasmania -- Deloraine; Folk music -- Tasmania -- Deloraine; Accordion music